Transaction Cost Heterogeneity in the Interbank Market and Monetary Policy Implementation under alternative Interest Corridor Systems - Thomas Link; Ulrike Neyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper introduces a theoretical model of an interbank market and a central bank that implements an interest corridor system in order to exert control over the overnight interbank rate. We analyze in how far interbank market frictions in the form of broadly defined transaction costs influence banks' demand for excess reserves and the interbank market outcome under different corridor regimes. The friction costs might stem from asymmetric information about counterparty credit risks, reflect differing borrowing/lending conditions in fragmented money markets, or result from new regulatory capital rules affecting interbank exposures. We show that the transaction cost effect on banks' demand for excess reserves and on the interbank market outcome, as well as the importance of bank transaction cost heterogeneity and of the corridor width in this context, depend crucially on whether the central bank runs a standard or a floor operating system.
Keywords: E52; E58; G21; 330